Implementasi Pembelajaran Neurosains dalam Menstimulasi Perkembangan Moral Anak Usia Dini - Hartin Kurniawati; Ika Rahayu Satyaninrum; Masithoh Sitompul; Muqita Zahira Al Faruq (STAI Al-Hamidiyah Jakarta, 2024)
The aim of this descriptive qualitative research is to describe how the implementation of neuroscience learning is used to stimulate children's moral abilities. The subjects in this research were the school principal and class teacher RA Assa'adah. Data collection techniques that is used was structured interviews. The research results show that education in early childhood is carried out through play activities, because it is in line with the natural nature of a child who likes to play. By playing, children gain knowledge spontaneously without feeling pressured or burdened. Neuroscience learning fits children's learning needs when it is done in a fun way. The media used is appropriate to the child's interests. The activity begins by conditioning the children through reading Iqra, Latin reading books, reading the pledge when lining up, moving and singing or playing simple games, as well as reading short letters together. This is done to prepare the children to be enthusiastic about learning, focus on learning, and receive learning material well. Activities to stimulate children's morals were carried out by singing Islamic songs, reciting hadiths, and telling stories of the prophet. The teacher will give a warning by reading a hadith if a child breaks the rules at school. Teachers assess children's moral development every day. The development results of each child are different because of the differentiation of the character and background of each child. The teacher will evaluate the activities that have been carried out and improve them for the next learning year, especially in terms of children's moral development.